Women's experiences of legitimacy, satisfaction and commitment as entrepreneurs: embedded in gender hierarchy and networks in private and business spheres. Issue 3 (15th March 2019) - Liu, Ye; Schøtt, Thomas; Zhang, Chuqing
ABSTRACT: When a woman perceives legitimacy in her job as an entrepreneur from networks that are often influenced by the gender hierarchy that grants men higher status than women, she is encouraged in her job. What are the effects of gender hierarchy and networks on the legitimacy a female entrepreneur perceives and on her satisfaction and commitment to the job? A sample of 5997 female entrepreneurs in the developing world was surveyed for Global Entrepreneurship Monitor. They were found to experience legitimacy as entrepreneurs in their networks in the private sphere and the business sphere. Gender hierarchy constrains legitimacy more in the private sphere than it does in the business sphere. Legitimacy in the business sphere can fulfil the need to feel competent and enhance job satisfaction, while legitimacy in the private sphere can fulfil the need to feel related and enhance job commitment. The account contributes to a two-level contextualization of experiences: micro-level embedding in networks that are nested in macro-level embedding in gender hierarchy.